1972
DOI: 10.1128/iai.5.4.482-490.1972
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Mycobacterial Antigens by Two-Dimensional Polyacrylamide Gel Electrophoresis

Abstract: Cell extracts and culture filtrates were prepared from several mycobacterial species and subjected to two-dimensional acrylamide gel electrophoresis. The cell preparations were first electrophoresed in a 7% homogeneous gel followed by a second electrophoresis, at right angles to the first separation, in a 2 to 30% linear gel gradient slab. Because the stained slab resembled a "fingerprint" or "peptide map," this procedure has been called "electroprotein mapping." More than 200 proteinstaining spots were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…(3), who showed that the IEP patterns of bacillary extracts were constant for a strain of tubercle bacilli regardless of the age of the culture. Similarly, the results of previous studies from one of our laboratories have indicated that sonic extracts prepared from different strains of a single mycobacterial species had essentially the same GAGE and 2-D IEP patterns; in contrast, the patterns of their culture filtrates varied markedly in most cases from strain to strain (1,22,(26)(27)(28). Also, as shown in the present study, the antigenic composition did not differ significantly when the disruption method was varied.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…(3), who showed that the IEP patterns of bacillary extracts were constant for a strain of tubercle bacilli regardless of the age of the culture. Similarly, the results of previous studies from one of our laboratories have indicated that sonic extracts prepared from different strains of a single mycobacterial species had essentially the same GAGE and 2-D IEP patterns; in contrast, the patterns of their culture filtrates varied markedly in most cases from strain to strain (1,22,(26)(27)(28). Also, as shown in the present study, the antigenic composition did not differ significantly when the disruption method was varied.…”
Section: Methodssupporting
confidence: 61%
“…However, because they are autolytic products and subject to continuous enzymatic alteration and degradation during incubation, the antigenic composition of culture filtrate preparations can vary markedly, not only between strains of tubercle bacilli but also between identical cultures of the same strain (3, 21, 26). Preparations of mycobacterial cytoplasmic extracts, in contrast, have been reported to be uniform in composition (3,6,21,22,(26)(27)(28). In other studies, bacillary extracts have been demonstrated to be suitable materials for immunological study.…”
mentioning
confidence: 99%
“…Provided that the physical conditions of acrylamide gel concentration, pH and buffer, and current flow are standardized, it provides a technique of powerful resolution that is readily adaptable to the identification and nomenclature of individual antigens. Moreover, the resolving power of gel electrophoretic techniques has been greatly increased by the two-dimensional procedures introduced by, among others, Augier and Augier-Gibory (9) and Wright and co-workers (202,203). As illustrated in Fig.…”
Section: Identification and Nomenclature Of Mycobacterial Antigensmentioning
confidence: 99%
“…The chemical extraction methods, employed for the preparation of whole cell-associated antigens, were used because similar methods, had been previously applied (6,9,11,(22)(23)(24)(25). Cytoplasmic antigens, obtained by preparative ultracentifugation of water extracts of cell lysates were examined because of their successful usage as antigens with mycobacteria (42,43) and Candida albicans (1, 2) for CIE studies. Reported advantages of plasma antigens of Actinomycetales for serological taxonomic studies of these bacteria (24) also contributed to the choice of the cytoplasmic fraction of cell lysates.…”
Section: Discussionmentioning
confidence: 99%